PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 101777 SAENTIS - Saragih, Vizulastri; Lubis, Wildansyah; Tamba, Robenhart; Perangin-angin, Laurensia; Usman, Khairul (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to determine the effect Numbered Head Together (NHT) Model on student learning outcomes in class IV SD NEGERI 1001777 Saentis. The research method used is Quasi-experimental or Quasi Experimental with a quantitative approach. The sample in this study was class IV A as the experimental class and class IV B as the control class at SDN 101777 Saentis, each class consisting of 50 students. The research instrument used was a test instrument consisting of 20 multiple choice questions. Based on the result of data analysis, the average pretest score for the experimental class was 48 and the control class was 48, while the average posttest score for the experimental class was 84 so that the application of Numbered Head Together (NHT) model can improve student learning outcomes. Based on this, it can be concluded that there is a significant influence from using Numbered Head Together (NHT) Model. Keywords : Numbered Head Together (NHT) Model, learning outcomes.